Smart learning environment, perceived usefulness, perceived ease of use and behavioral intention in UAE education - Al-Naqbi, Faisal Abdullah Saeed (Tanjong Malim, 2023)
Smart learning environment, perceived usefulness, perceived ease of use and behavioral intention in UAE education by Al-Naqbi, Faisal Abdullah Saeed